2012
DOI: 10.1186/1471-2202-13-32
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic nanoparticles in primary neural cell cultures are mainly taken up by microglia

Abstract: Background Magnetic nanoparticles (MNPs) offer a large range of applications in life sciences. Applications in neurosciences are one focus of interest. Unfortunately, not all groups have access to nanoparticles or the possibility to develop and produce them for their applications. Hence, they have to focus on commercially available particles. Little is known about the uptake of nanoparticles in primary cells. Previously studies mostly reported cellular uptake in cell lines. Here we present a syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
69
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 60 publications
10
69
0
1
Order By: Relevance
“…Parallel derivation of all glial types for the model from a single primary source, as achieved here, avoids problems with cell lines which are often of unknown provenance (origin and treatment history) 31 and altered physiology, 32 potentially leading to dramatically different nanoparticle uptake dynamics and toxicity profiles compared with primary cells. 16 Our method also ensures that constituent cells possess identical ages/anatomical origins, with culture under identical conditions. Further, by achieving defined cellular stoichiometry with high reproducibility, direct intercellular comparisons can be reliably drawn.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parallel derivation of all glial types for the model from a single primary source, as achieved here, avoids problems with cell lines which are often of unknown provenance (origin and treatment history) 31 and altered physiology, 32 potentially leading to dramatically different nanoparticle uptake dynamics and toxicity profiles compared with primary cells. 16 Our method also ensures that constituent cells possess identical ages/anatomical origins, with culture under identical conditions. Further, by achieving defined cellular stoichiometry with high reproducibility, direct intercellular comparisons can be reliably drawn.…”
Section: Discussionmentioning
confidence: 99%
“…12 In terms of widely used current approaches, live animal models are biologically relevant but involve significant ethical issues, technical complexity and expense, whilst being low-throughput. 16 and reducing their predictive utility.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] SPIOs are taken up by activated microglia in primary and mixed cell cultures in a time-, concentration-, and temperaturedependent manner. 21,22 This raises the possibility of sustained microglial activation that can prove to be severely disruptive to neural function. [23][24][25] Interestingly, other studies have demonstrated that cellular reactions critically depend on the respective particle properties, including composition, size, and biocompatibility.…”
Section: Iron Oxide Nanoparticlesmentioning
confidence: 99%
“…Microglia have been shown to dominate uptake versus other neural cell types due to their comparatively rapid and extensive particle uptake profiles [9]. This has been demonstrated for different NP types, using defined glial co-cultures [9], undefined co-cultures of primary neurons and glial cells, and more complex transverse organotypic spinal cord slices (intact tissue) co-cultured with peripheral nerve grafts [10]. Together, it is estimated that the glial cells account for up to 99.5% of cellular uptake of NPs, with microglia shown to be responsible for the majority of this uptake in vivo [11].…”
Section: Introductionmentioning
confidence: 99%